2011
DOI: 10.1111/j.1473-2165.2011.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study to evaluate the depigmenting activity of l-ascorbic acid plus phytic acid - serum vs. placebo on solar lentigines

Abstract: Study treatment was significantly more efficacious than vehicle in many respects and was well tolerated. Future, larger studies are needed to confirm these results and to compare the product with gold standard treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In order to respond to the need for a more robust approach in measuring the effectiveness of a lightening topical product, the present study proposes a unique design including clinical, digital and subjective analyses. Further, most studies on lentigines are performed over a short period of up to 3 months [17,1922], and with a limited number of enrolled subjects, with an average of 10–20 subjects per study [19,23]. The current study design included a longer follow up of 12 months, enabling the consideration of seasonal impact on lentigines pigmentation on a relatively large population cohort of 36 subjects and a total of 72 lentigines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to respond to the need for a more robust approach in measuring the effectiveness of a lightening topical product, the present study proposes a unique design including clinical, digital and subjective analyses. Further, most studies on lentigines are performed over a short period of up to 3 months [17,1922], and with a limited number of enrolled subjects, with an average of 10–20 subjects per study [19,23]. The current study design included a longer follow up of 12 months, enabling the consideration of seasonal impact on lentigines pigmentation on a relatively large population cohort of 36 subjects and a total of 72 lentigines.…”
Section: Discussionmentioning
confidence: 99%
“…Color measurement can quantify the visual perception of colors. It has been shown to be a precise and robust technique for skin lightening efficacy evaluation [8,22,27,39]. Pierre Fabre imaging team previously showed that precise skin color measurements can be performed using a high-magnification color-calibrated camera, also used to follow up lentigines [20].…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10][11] Treatment with other de-pigmenting agents as 10% L-ascorbic acid + 2% phytic acid have also been reported. 12 Post-inflammatory hyperpigmentation is a frequent concern when treating solar lentigines, 5,6 mainly in darker skin photo-types and in patients with history of PIH. Its prevalence does not vary according to age or gender.…”
Section: Introductionmentioning
confidence: 99%
“…Topical products with adapalene and a fixed combination of mequinol (2%) and tretinoin (0.01%) have been reported as effective treatments, being an alternative to ablative procedures . Treatment with other de‐pigmenting agents as 10% l ‐ascorbic acid + 2% phytic acid have also been reported …”
Section: Introductionmentioning
confidence: 99%